Improving the True Cycling of Redox Mediators‐assisted Li‐O2 Batteries. Issue 2 (5th April 2021) - Cao, Deqing; Yu, Fengjiao; Chen, Yuhui; Gao, Xiangwen
Abstract : The application of redox mediators has been considered as a promising strategy to boost the performance of aprotic Li‐O2 batteries. However, the issues brought with redox mediators, especially on the Li anode side have been overlooked. Here, we propose a facile approach of preparing a gel polymer membrane that not only allow uniform Li plating/stripping with large current densities over extended cycling but also inhibit the diffusion of redox mediators and avoid redox shuttling, self‐discharge, and internal short‐circuiting. More importantly, the gel polymer membrane prevents the penetration of O2 and superoxide intermediates from the Li anode. Therefore, it ensures the successful application of both lithium anode and redox mediators in Li‐O2 batteries to achieve the desired high capacity and rate performance. Meanwhile, it helps understand the benefit and problems of added redox mediators and reactive oxygen species so that the performance of such Li‐O2 batteries can be truly evaluated. Abstract : We prepared a gel polymer membrane that could prohibit the redox shuttle of redox mediators as well as the penetration of oxygen related species. This not only protects the lithium negative electrode but also improves the performance of the lithium oxygen batteries.